Predictors of client satisfaction with family planning services in Ethiopia: a systematic review and meta-analysis - Ayale Ferede, Yeshiwas; Tassew, Worku Chekol; Zeleke, Agerie Mengistie (Frontiers in Global Women's Health, 2025)
BackgroundThe use of modern contraceptives by married Ethiopian women has increased over the past 15 years. Despite a few studies reporting different predictors of satisfaction with family planning services, there is a lack of nationwide data showing the determinants of client satisfaction with family planning services. Thus, this meta-analysis aimed to determine the predictors of client satisfaction with family planning services in Ethiopia.MethodsFrom January 20 to March 10, 2024, a thorough search of the literature was conducted using PubMed, Web of Science, EMBASE, CINAHL, and Google Scholar. The quality of the included studies was assessed using the critical assessment checklist developed by the Joanna Briggs Institute (JBI). The statistical program Stata 11 was used to carry out the analysis. Using Cochran's Q-statistic, heterogeneity was statistically assessed and measured by the I2 value. If significant heterogeneity was found across the included studies, a random effects model was used to assess the factors influencing client satisfaction with family planning services. Otherwise, a fixed-effects model was employed.ResultsIndependent factors influencing clients' satisfaction with family planning services included waiting times of less than one hour (POR = 4.37; 95% CI: 2.05, 9.32), ensuring privacy (POR = 6.31; 95% CI: 2.78, 14.28), convenient opening hours (POR = 5.91; 95% CI: 1.61, 21.63), education level above primary school (AOR = 2.61; 95% CI: 1.02, 6.68), being informed about side effects (AOR = 3.08; 95% CI: 1.22, 7.74), and receiving adequate information (POR = 4.2; 95% CI: 1.87, 9.44).ConclusionThe findings indicate that key factors significantly influencing client satisfaction with family planning services include reduced waiting times, privacy protection, convenient service hours, higher education levels, being informed about potential side effects, and receiving comprehensive information. These elements are critical for improving satisfaction and should be prioritized in family planning services. As a result, Ethiopian policymakers and decision-makers must devise plans to maximize client satisfaction with healthcare services through client-centered care.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=563937, PROSPERO (CRD42024563937).